Fault-Tolerant Distributed Computing for Real-Time Applications in Critical Systems (International Journal of Scientific Research and Management (IJSRM), 2020)
Distributed computing particularly, fault tolerant systems has indispensable functionality in maintaining the dependability and availability of the actual time applications across various sectors including but not limited to healthcare, aerospace, transportation, and industrial control systems. Such systems should run continuously, though there may be equipment problems or network interruptions and software glitches. The major concepts, ways and issues concerning fault-tolerant distributed computing for real time applications in safety critical systems have been discussed in this paper. They include redundancy, replication, consensus algorithms, error detection, and recovery strategies, about which the course notes stress how they ensure that system integrity is sustained during failure modes in addition to satisfying real-time constraints. Exploiting case analysis, we consider fault-tolerant application of these approaches in different sectors as critical environments with an acute necessity for fault-tolerance mechanisms. The paper also presents present day problems such as scalability, performance in fault conditions, and the effectiveness/cost ratio. Last, a consideration of future work in self-organizing and self-healing frameworks that incorporate machine learning, quantum computing, and such other related technologies aimed at achieving better fault tolerance for real-time, distributed systems is made. The role of building and designing infallible, high availability system redundancy models for the assurance of safety, speed, and uninterruptible functionality of such systems is further highlighted by this work.